Examining Students' Perceptions and Expectations of Islamic Economics in Addressing Social Inequality - Hadi, Kuncoro (Global Review of Islamic Economics and Business, 2025)
This study examines how university students in Jakarta perceive and expect Islamic economics to address social inequality. Integrating Social Cognitive Theory (SCT) and Expectation-Confirmation Theory (ECT), it proposes a cognitive-affective-conative framework linking students’ understanding, perception, and expectation. A survey involving 522 students was analyzed using PLS-SEM. Results confirm that understanding significantly influences perception (β = 0.403) and expectation (β = 0.185), with perception also mediating the relationship (β = 0.189). Students largely view Islamic economics as fair and effective, especially instruments like zakat and Islamic microfinance. However, gaps exist between expectations and implementation, driven by limited public understanding, inadequate regulation, and digital infrastructure challenges. This research contributes to theoretical integration of SCT–ECT in Islamic economics and provides actionable insights for policymakers and educators to strengthen financial literacy, reform regulations, and enhance technological access. The findings support a dual approach: conceptual literacy and perceptual alignment are both essential to realize the role of Islamic finance in promoting equity.